Pengaruh Orientasi Pesaing, Orientasi Konsumen dan Peran Pemerintah terhadap Kinerja Pemasaran UMKM pada Wisata Kuliner Oepoi Kupang dengan Keunggulan Bersaing sebagai Variabel Intervening - Elis Islani Ruchiyat; Henny A. Manafe; Simon Sia Niha; Anggraeny Paridy (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
The research entitled The Influence of Competitor Orientation, Consumer Orientation and Government Role on MSME Marketing Performance in Oepoi Kupang Culinary Tourism with Competitive Advantage as Intervening Variables is intended to determine the direct and indirect effects of competitor orientation, consumer orientation, the role of government and competitive advantage on marketing performance UMKM Culinary Tourism in Oepoi Kupang. The type of research used is quantitative with partial least squares (PLS) analysis and uses the Smarts PLS 3.0 software. From the results of the analysis and discussion, competitor orientation has a significant impact on the marketing performance of MSMEs in Oepoi, Kupang City. Competitor orientation is not important enough for the competitive advantage of UMKM in Kupang City, consumer orientation is not important enough for the marketing performance of UMKM. Consumer orientation is quite important for the competitive advantage of Kupang City SMEs.